Juxtaposition of Western Pacific Subtropical High on Asian Summer Monsoon Shapes Subtropical East Asian Precipitation. Issue 3 (10th February 2020) - Xu, Hai; Goldsmith, Yonaton; Lan, Jianghu; Tan, Liangcheng; Wang, Xulong; Zhou, Xinying; Cheng, Jun; Lang, Yunchao; Liu, Congqiang
Abstract: Increasing lines of evidence question the homogenous response of Asian Summer Monsoon (ASM) precipitation patterns, requiring rethinking of the forcing mechanisms. Here we show a 15, 000‐year quantitative precipitation history based on well‐dated lake levels at Lake Chenghai, subtropical China. Lake levels and the inferred precipitation were high during the Bølling‐Allerød, early and late Holocene, but low during the middle Holocene. The orbital scale precipitation trend is out of phase with boreal summer insolation, the later has been widely suggested as the driver of ASM precipitation. Lake Chenghai long‐term lake levels are synchronous with trends in tropical Pacific sea surface temperatures, the related zonal sea surface temperature gradients, and interhemispheric temperature gradients. We propose that changes in either the interhemispheric or zonal Pacific temperature gradients modulate the intensity and location of the western Pacific subtropical high, which is juxtaposed on the ASM, leading to heterogeneous hydroclimatic conditions over subtropical East Asia. Plain Language Summary: We present a 15, 000‐year record of southern China precipitation based on well‐dated ( n =130 radiometric ages) lake level variations of a closed basin lake. The reconstructed long‐term southern China precipitation trend is out of phase with boreal summer insolation, which has been shown to drive ASM precipitation, but broadly follows trends in tropical Pacific sea surface temperatures (SSTs), the related zonal SST gradients, and interhemispheric temperature gradients. We propose that changes in either the interhemispheric or zonal Pacific temperature gradients modulate the intensity and location of the western Pacific subtropical high and are juxtaposed on the ASM, leading to heterogeneous hydroclimatic conditions over subtropical East Asia, including an unexpected southern China mid‐Holocene drought. The results of this study are unique in that (1) precipitation was robustly reconstructed from beach evidence, which is a first‐order measure of the balance between rainfall amount and evaporation. (2) A new mechanism driving long‐term precipitation changes over subtropical East Asia is proposed. Providing the mechanism stands, increasing SST gradients under the expected global warming scenario could enhance the role of western Pacific subtropical high and lead to less precipitation over subtropical East Asia. Key Points: A 15, 000‐year precipitation history over subtropical China was reconstructed based on well‐dated ( n =130 radiometric ages) lake levels Subtropical China precipitation trend does not resemble Asian summer monsoon trend but is synchronized with trends in tropical Pacific SST Juxtaposition of western Pacific subtropical high on Asian summer monsoon could have shaped the subtropical East Asian precipitation